Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Kinerja Karyawan Pada PT. Mandiri Konstruksi di Tangerang Selatan - Dodi Prasada (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study aims to determine the effect of leadership style and organizational culture on employee performance at PT. Independent Construction in South Tangerang. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study, Leadership Style has a significant effect on employee performance by 51.4%, hypothesis testing is obtained t count> t table or (7.276> 2.009). Organizational culture has a significant effect on employee performance by 43.6%, hypothesis testing is obtained t count> t table or (6.215> 2.009). Leadership Style and Organizational Culture simultaneously have a significant effect on employee performance with the regression equation Y = 8.292 + 0.418X1 + 0.379X2 and the influence contribution is 61.7%, hypothesis testing obtained F count> F table or (39.529> 2.790).